ATM network performance under bursty traffic environment - Tay, Eng Kiat. (2008)
In this project dissertation, the performance of an ATM network under bursty traffic environment is studied. The bursty traffic is proposed to be generated mainly by on/off traffic sources coupled with background constant rate traffic (CBR). This kind of traffic simulates the multimedia traffic that supported by B-ISDN. The ATM switch architecture modeled is the non-blocking type with output buffer. The simulation program is developed using Network 11.5 to obtain performance criteria such as cell transfer delay (CTD), cell delay variance (CDV) and cell loss ratio (CLR) under varying bursty conditions. These major performance criteria would be used in ATM network planning in terms of node and link capacity assignment.